Improved Predictive Power Control Algorithms to Increase CDMA System Capacity - A. Kurniawan; Iskandar Iskandar; Sayid Machdar (Institute for Research and Community Services, Institut Teknologi Bandung, 2009)
In this paper capacity of CDMA system is evaluated using an improved algorithm of channel prediction-based power control in Rayleigh fading channel environments. One of the most serious problems which degrades the performance of power control algorithm is the effect of feedback delay. To overcome the effect of feedback delay, power control algorithm relies on channel prediction techniques, which utilize the correlation property of the past channel measurements. In CDMA power control, however, the correlation property of channel measurements is destroyed because the transmit power is continuously updated for each power control interval. In order to restore the correlation property of the channel, the past channel measurements are compensated for by the same factors that were given by power updating for each power control interval. The prediction algorithm in this paper is proposed using the least mean square (LMS) technique. The result shows that the capacity of CDMA systems increase significantly when the improved predictive algorithm is used. Numerical evaluation shows that CDMA capacity increases by more than 40 % for fixed step algorithm and more than 50 % for variable step algorithm when the proposed algorithm is employed.